A Development of Youth Drama Activities to Enhance the Awareness of Lamphun Identity - Songketkun, Peeranat; Inchan, Noppadol (Community and Social Development Journal, 2020)
The purpose of this research is to develop the Youth drama activities to enhance the awareness of Lamphun identity and to compare the results of the used of Youth drama activities to enhance the awareness of Lamphun identity. Conducted by in-depth interviews and the development of the Youth drama activities by using the information obtained from in-depth interviews. Applied with a sample of 40 students in Mae Tha Witthayakhom School, use a simple random sampling divided into 2 groups, the experimental and the control group. The result is found that; 1) There are 4 identities of Lamphun Phra Nang Cham Devi, Phra That Hariphunchai Temple, Than Salak Yom and Lamphun woven fabric 2) The form of the Youth drama activities to enhance the awareness of Lamphun identity based on the principles of Creative Drama Activity and Drama in Education (DIE) has a total of 10 activities, including Welcome to Lamphun, Phra Nang Cham Devi the first queen of Hariphunchai, From Lavo to Lamphun, Temple and Palace, Lamphun’s Heart Center, Than Salak Yom the only one tradition in the world at Lamphun, The merit tree of the stratagem, Lamphun woven fabric from palace to villagers, Wearing clothes-playing-as a drama And We love Lamphun, which take 5 weeks period, 2 times a week, 50 minutes each time. The result was submitted considered and reviewed on the IOC by a group of experts found that the Youth drama activities to enhance the awareness of Lamphun identity had the level of 0.66-1.00 and suitable to be applied. 3) The result comparison of the applied of the Youth drama activities to enhance the awareness of Lamphun identity found that the awareness level in Lamphun identity before the experiment, the experimental group and the control group were not significantly different at the .05 level and the awareness level in Lamphun identity after the experiment of the experimental group was higher than the control group with statistically significant differences at the .05 level. The awareness of the Lamphun identity of the experimental group before the experiment was at a medium level and after the experiment was at the highest level.